Out of Africa - Sydney Pollack; Thiaka, Joseph; Klaus Maria Brandauer; Malick Bowens; Michael Kitchen; Robert Redford; Stephen Kinyanjui; Meryl Streep (USA Universal Studios, 1985)
Follows the life of Karen Blixen, who establishes a plantation in Africa. Her life is Complicated by a husband of convenience (Bror Blixen), a true love (Denys), troubles on the plantation, schooling of the natives, war, and catching VD from her husband.
In 20th century colonial Kenya, a Danish baroness/plantation owner has a passionate but ultimately doomed love affair with a free-sprited big-game hunter.
Karen Blixen
Languages : English
Subtitles : Turkish, English, Bulgarian
1985 Oscar Academy Award Best Picture
Keywords: Drama; Romance; Biography -- Oscar Academy Award